Disruption of Two-component System LytSR Affects Forespore Engulfment in Bacillus thuringiensis - Peng, Qi; Wu, Jianbo; Chen, Xiaomin; Qiu, Lili; Zhang, Jie; Tian, Hongtao; Song, Fuping (Frontiers in Cellular and Infection Microbiology, 2017)
Two-component regulatory systems (TCSs) play pivotal roles in bacteria sensing many different stimuli from environment. Here, we investigated the role of the LytSR TCS in spore formation in Bacillus thuringiensis (Bt) subsp. kurstaki HD73. lacZ gene fusions revealed that the transcription of the downstream genes, lrgAB, encoding two putative membrane-associated proteins, is regulated by LytSR. The sporulation efficiency of a lytSR mutant was significantly lower than that of wild-type HD73. A confocal microscopic analysis demonstrated that LytSR modulates the process of forespore engulfment. Moreover, the transcription of the lytSR operon is regulated by the mother-cell transcription factor SigE, whereas the transcription of the sporulation gene spoIIP was reduced in the lytSR mutant, as demonstrated with a β-galactosidase activity assay. These results suggest that LytSR modulates forespore engulfment by affecting the transcription of the spoIIP gene in Bt.